Diversity Issues in Academic Reform - Cunningham, George B. (Journal of Intercollegiate Sport, 2012)
The purpose of this paper was to provide a response to the Petr and McArdle (2012) and Paskus (2012) papers. The author suggests that academic reform should be couched within broader diversity issues affecting intercollegiate athletics, with a particular emphasis on race, social class, and the ability to implement reforms. Implications and conclusions are discussed.